Nursing Care Delivery Models and Intraprofessional Collaborative Care: Canadian Nurse Leaders' Perspectives - Dawn Prentice RN, PhD; Jane Moore RN, PhD; Bruna Fernandes RN, BScN; Emma Larabie RN, BScN (SAGE Publishing, 2022)
Introduction There are many different types of nursing care delivery models used to organize and provide care in hospitals. These models are comprised of different organizational structures and staffing skill mixes. Objective The aim of this study was to explore how nursing care delivery models promote intraprofessional collaborative care in acute care hospitals from the perspectives of nurse leaders. Methods A qualitative descriptive approach was used for this study. Telephone interviews were conducted between January 2021 and August 2021 using an interview guide comprised of semi-structured and structured questions. Using a purposeful sampling technique, ten leaders from nine hospital systems, representing both urban and rural hospitals in the province of Ontario, Canada, participated in the study. Content analysis was conducted resulting in two overarching themes. Results The first theme, Fluidity of the Model addresses the flexibility of the models and the impact of contextual factors such as changes in nurses' scope of practice, government funding changes, staffing mix, and organizational policies and rules. The second theme, Tools of the Trade describes the resources that hospitals implement to promote intraprofessional collaboration that indirectly impacts on patient safety. Conclusion Nursing care delivery models need to be flexible and adaptable. All nursing care delivery models in this study used various tools to promote intraprofessional collaborative care.